Synthesis of Highly Ordered Mesoporous MCM-41: Selective External Functionalization by Time Control - Silva,Ana Claudia P. da (2019)
Sol-gel synthesis is commonly used to modify the surface of mesoporous silica nanoparticles (MSN) with organic groups through the co-condensation method. The template removal, and the site-controlled addition of organic groups and their partial occlusion inside the framework walls are still a challenge in the one-pot synthesis. Here, we optimize the synthesis of amino-modified MSN by the combination of efficient template removal methodology with the precise time of the amino precursor addition to achieve superb mesoporous material. The addition after the growth process produces a sample with a significantly higher amount of NH2 on the external surface when compared to the standard procedure. The template removal by reflux with isopropanol/H+ eliminated ca. 90% of cetyltrimethylammonium bromide (CTAB), and preserved the mechanical and thermal properties, even with thin walls (2.1 nm). The synthesized nanoparticles possess stability, appropriate size, and a positive surface. This makes them excellent nanocarriers, especially in the biomedical field.